WORD RECOGNITION SPEED IN ENGLISH LITERATURE STUDENTS: A LEXICAL DECISION STUDY - Made Evania Althea Holy; I Wayan Arka; I Gusti Ngurah Parthama (Loquēla (Journal of Linguistics, Literature, and Education), 2025)
The lexical decision task was used in this study to evaluate the cognitive processes of word processing in English Literature students. This study focuses into the distinctive characteristics of word processing in people who are proficient in English literature, specifically how their literary analytical abilities impact lexical judgment problems. The goal was to investigate how linguistic information gained via literary study affects word processing. The web-based PsyToolkit program was used to record response times and accuracy.  Ten English literature students took part in a web-based lexical judgment exercise that required them to differentiate between actual and non-words. The results show that reaction times differ between three stimulus categories: related words, unrelated words, and nonsense words. The findings of this study demonstrate that participants responded faster to related words, suggesting a beneficial impact of semantic connection. However, equal response times for unrelated and nonsense words imply similar categorization problems. These findings provide connection between semantic processing and lexical decision-making, highlighting the significance of semantic priming in word recognition.